STRUKTUR DAN KOMPOSISI VEGETASI POHON DI HUTAN LINDUNG GUNUNG MAHAWU DAN HUTAN LINDUNG GUNUNG MASARANG - Elisabeth Luturyali; Martina A. Langi; Maria Y.M.A. Sumakud (COCOS, 2019)
AbstractThis research aims to study the structure and composition of forest tree vegetation in the protected forests of Mount Mahawu and Mount Masarang. Line Method was used to study the changes in tree distribution based on the topography and elevation. Plots measuring 20 x 20 m2 are made following topographic lines (mountain slopes). The results show that the structure and composition of the dominant trees in the Mahawu Protection Forest are different from that of the Masarang Protection Forest. The dominant species in the Mahawu Protection Forest are Diospyros celebica, followed by Ficus septica and Anthocephalus chinensis; while in the Masarang Protected Forest Artocarpus sp. followed by Ficus septica and Lansium sp.Keywords: forest tree structure, forest tree composition, Mount Mahawu, Mount Masarang, protected forest